PENGARUH ANGGARAN WAKTU AUDIT, KOMPLEKSITAS DOKUMEN AUDIT DAN PENGALAMAN AUDITOR TERHADAP PERTIMBANGAN AUDIT SAMPLING PADA BADAN PEMERIKSAAN KEUANGAN (BPK) REPUBLIK INDONESIA PERWAKILAN PROVINSI ACEH - Nadirsyah Nadirsyah; Mirna Indriani; Iskandar Usman (Jurnal Telaah dan Riset Akuntansi, 2011)
This research is done at BPK branch office Aceh Province  which aim to know the influence of time budget audit, complexsity of audit document and audit experience toward judgement audit sampling either simultaneously or partially.        Responden of this research is auditors at BPK branch office Aceh Province.  The objective of this research is to be able to seek the causality between the time budget audit, complexsity of audit document and audit experience toward judgement audit sampling with 56 auditors samples of populations 99 auditors who is taken at stratified random sapling. Technics of data analysis  used is multiple linears regression.       Result of this research indicate that the time budget audit, complexsity of audit document and auditor experience by simultaneously have significan influence toward judgement audit sampling. By partially just time budget audit have significan influence toward judgement audit sampling, but complexsity of audit document and auditor experience do not have significan influence toward judgement audit sampling.  Keyword : time budget audit, complexsity of audit document, auditor experience and judgement audit sampling.